Development of a model for the integration of web 2.0 services based on education 3.0 (Ingenio Magno, 2016)
The phenomenon of globalization presents increasingly great challenges to communities, which requires them to have a great variety of physical and technological resources available to be carried out; for a long time, education has played an especially relevant role concerning the behavior and development of the individual and the community in general, which is why governments all over the world have focused their efforts on devising an education model that is able to be extended to each member of society, which makes up for the requirements imposed by the stated phenomenon and at the same time provides incentive for the development of new knowledge abilities in students. Colombia is a developing country that still has not officially incorporated the 3.0 technology in its educational regulations, which causes a significant delay in educational matters and training regarding fully fully developed countries such as Spain, Mexico, or the United States; this article presents an integration model for web 2.0 services based on education 3.0 in the context of guidelines and definitions of secondary school education in Colombia, which could be considered a step toward the full virtualization of the same.
Keywords: education 3.0; mobile education; virtual education; services integration model; web 2.0